Ablation of Outflow Tract Arrhythmias in Patients With and Without Structural Heart Disease—A Comparative Analysis - Schleberger, Ruben; Riess, Jan; Brauer, Anika; Pinnschmidt, Hans O.; Rottner, Laura; Moser, Fabian; Moser, Julia; Kany, Shinwan; My, Ilaria; Lemoine, Marc D.; Reissmann, Bruno; Meyer, Christian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Catheter ablation of ventricular arrhythmias emerging from the ventricular outflow tracts and adjacent structures is very effective and considered almost curative in patients without structural heart disease (SHD). Outcomes of patients with SHD undergoing ablation of outflow tract arrhythmias are not known. Methods Consecutive patients (2019–2021) undergoing catheter ablation of ventricular arrhythmias in a single high-volume center were retrospectively analyzed. Patients with ablation of outflow tract arrhythmias were identified and divided in individuals with and without SHD. Procedural parameters and acute outcome were compared. Results We identified 215 patients with outflow tract arrhythmias (35.3% female, mean age 58.3 ± 16.0 years). Of those, 93 (43.3%) had SHD. Patients with SHD and outflow tract arrhythmias were older (65.0 ± 12.8 vs. 53.3 ± 16.3 years; p < 0.001), more often male (82.8 vs. 50.0%; p < 0.001) and had more comorbidities than patients without SHD (arterial hypertension: 62.4 vs. 34.4%, p < 0.001; diabetes: 22.6 vs. 8.2%, p = 0.005; chronic lung disease: 20.4 vs. 7.4%, p = 0.007). Outflow tract arrhythmias in patients with SHD had their origin more often in the left ventricle (68.8 vs. 53.3%, p = 0.025). The acute success rate was similar in both patient groups (93.4 vs. 94.2%, p = 0.781). Patients with SHD were discharged later median length of hospital stay with SHD 5 [6 (interquartile range)] days, without SHD 2 [4] days, p < 0.001. Periprocedural complications were numerically more frequent in patients with SHD [with SHD 12 (12.9%), without SHD 8 (6.6%), p = 0.154]. Conclusion Outflow tract arrhythmia ablation has a high success rate irrespective of the presence of SHD. Longer hospital stay and potentially a higher risk of periprocedural complications should be considered when discussing this treatment option with patients.